Panic Buying in Bangladesh: An Exploration of Media Reports - Arafat, S. M. Yasir; Yuen, Kum Fai; Menon, Vikas; Shoib, Sheikh; Ahmad, Araz Ramazan (Frontiers in Psychiatry, 2021)
Background: As an erratic human behavior, panic buying is an understudied research area. Although panic buying has been reported in the past, it has not been studied systematically in Bangladesh. Aim: This study aimed to explore the characteristics of panic buying episodes in Bangladesh in comparison to current concepts. Methods: A retrospective and explorative search were done using the search engine Google on November 6, 2020, with the search term “panic buying in Bangladesh.” All the available news reports published in the English language were extracted. A thorough content analysis was done focusing on the study objectives. Results: From the initial search, a total of 30 reports were extracted. However, six reports were not included based upon the exclusion criteria, resulting in an analysis of 24 reports. Five panic buying episodes were identified, discussing the precipitating events, responsible factors, goods acquired through panic buying, and prevention measures. Flood, curfew, COVID-19, and export ban were found to be precipitating events. Media reports frequently mentioned prevention strategies, expert opinion, supply chain status, rationing, and government action. The reported goods that were panic bought were items necessary for daily living such as rice, oil, spices, and safety products such as hand sanitizer and masks. Conclusion: The study revealed preliminary findings on panic buying in Bangladesh; however, they are aligned with the current concept of it. Further empirical studies are warranted to see the geographical variation, precise factors, and to test the culturally appropriate controlling measures.